Fecal egg counts for Kinnaura livestock and Asiatic Ibex in Pin Valley India - Khanyari, Munib (Dryad, 2021)
Disease cross-transmission between wild and domestic ungulates can have
negative impacts on agricultural economies and wildlife conservation.
Assessing how to reduce these impacts is key to maintaining people’s
livelihoods while also conserving wild ungulate populations. In the
trans-Himalayan region of Pin valley, migratory flocks of sheep and goats
share pastures seasonally with the resident wild ungulate, Asiatic ibex
(Capra sibirica), leading to the possibility of disease
cross-transmission. We focused our work on gastro-intestinal nematode
(GINs) as they are common determinants of health and fitness in wild and
domestic ungulates. Using a parasite life cycle model that incorporated
host movements and the effects of weather on infective larval
availability, we investigated the transmission dynamics and evaluated
potential interventions to attenuate infection pressure for both, the
livestock and ibex. We found that although ibex used the pastures
year-round, parasite eggs which they shed only contributed to infective
larvae on pastures during the summer. Migratory livestock enter the Pin
pastures around day 152 (i.e. 1st June) and subsequently contribute eggs
and hence infective larvae onto pasture. Migratory livestock were
predicted to contribute the majority of infective larvae onto shared
pastures, driving infections in both livestock and ibex. Our model
predicts that any amount of anti-parasitic treatment of migratory
livestock resulted in some reduction in infection pressure, but we found a
c.30 day intervention towards the end of the livestock’s time in Pin had
the highest impact, and is likely to be effective in reducing GIN burdens
in both domestic and wild hosts. Our study provides a transferable
multi-pronged approach and an adaptable predictive model to investigate
parasite transmission in multi-use landscapes, including those with
migratory hosts. We provide a robust approach for hypothesis-testing and
intervention design which can serve the dual purpose of conserving wild
ungulates and protecting herders’ livelihoods.